2020
DOI: 10.18632/aging.102931
|View full text |Cite
|
Sign up to set email alerts
|

Using ESTIMATE algorithm to establish an 8-mRNA signature prognosis prediction system and identify immunocyte infiltration-related genes in Pancreatic adenocarcinoma

Abstract: Objective: The tumour microenvironment is one of the significant factors driving the carcinogenesis of Pancreatic adenocarcinoma (PAAD). However, the underlying mechanism of how the tumour microenvironment impacts the prognosis of PAAD is not completely clear. Results: The transcriptome and clinical data of 182 PAAD program cases were downloaded from the TCGA database. Three hundred thirty-three differentially expressed genes (DEGs) between high and low stromal groups and 314 DEGs between high and low immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 48 publications
0
58
0
Order By: Relevance
“…Compared to the reported signatures, the uniqueness of this study was that LASSO regression analysis could execute feature selection and shrinkage and screen highly correlated genes, which determined the optimal genes to participate in subsequent signature building [66]. LASSO regression could prevent the gene signature overfitting and increase the accuracy of bioinformatics analysis [67]. We explored both ROC curve and test verification to assess the prognostic performance of the signature.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the reported signatures, the uniqueness of this study was that LASSO regression analysis could execute feature selection and shrinkage and screen highly correlated genes, which determined the optimal genes to participate in subsequent signature building [66]. LASSO regression could prevent the gene signature overfitting and increase the accuracy of bioinformatics analysis [67]. We explored both ROC curve and test verification to assess the prognostic performance of the signature.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that infiltrating immune cells can be isolated from tumors suggesting that tumor immune infiltration is a crucial biological process that occurs as a result of immune cell migration from the blood into the TME ( Ge et al, 2019 ; R. Liu et al, 2020 ). Multiple reports have suggested that the proportion and functional alterations of different tumor infiltrated immune cells contribute to the initiation and progression of PAAD ( Meng et al, 2020 ; Tian et al, 2020 ). However, the regulatory mechanisms of immune cells, stromal components of TME, and tumor immune infiltration in PAAD remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The ESTIMATE algorithm is employed to calculate the immune score and stromal score based on immune genes and stromal genes in the TME, which can be utilized to reflect the purity of the tumor [ 34 , 35 ]. In this study, we utilized this algorithm to evaluate the score of stromal and immune-related cells from LUAD patients in the TCGA database.…”
Section: Discussionmentioning
confidence: 99%